Pengaruh Terapi Sensori Integrasi pada Anak Autis yang Mengalami Gangguan Sensori di Pusat Layanan Autis Provinsi Bangka Belitung - Wahyu Kurniawan; Merlinda Juvita (MAWA IZH JURNAL DAKWAH DAN PENGEMBANGAN SOSIAL KEMANUSIAAN, 2019)
This study focuses on determining whether an influence of the application of sensory integration in autistic children in an autism service center of the Bangka Belitung island province. The hypothesis proposed is that there is a difference between before and after sensory integration. Subjects before being given sensory integration experienced a level of sensory disturbance that tended to increase compared to before being given treatment. The design used in this study is a single case study in the form of the effect of giving sensory integration therapy treatment. The analytical method used is analysis, visual inspection, interviews and non-parametric observation and analysis (Wilcoxon). The results of hypothesis testing on this therapy are Z = 0.034 (p> 0.05). Based on the analysis, it means that there is a difference in the decrease in the frequency of sensory disturbances between before and after sensory integration therapy in students in the autistic service center of Bangka Belitung province.